The Pathophysiology and Treatment of Polycystic Ovarian Syndrome: A Systematic Review - Gerry Wonggokusuma (Cermin Dunia Kedokteran, 2014)
Polycystic Ovary Syndrome (PCOS) is one of the most common endocrinopathies, affecting 5-10% of women of reproductive age. Diagnosis is based on European Society of Human Reproduction and Embryology and the American Society for Reproductive Medicine Consensus. A complete understanding of PCOS pathophysiology is still elusive. The heterogeneity of the syndrome reinforces its multifactorial nature, and pinpointing the etiologic factor is not yet possible; treatment focuses on clinical improvement based on the goals of patient and clinician. The use of insulin-sensitizing medications such as metformin recently has become an area of great interest. Its use may reduce the risk of hyperinsulinism, type 2 diabetes, and metabolic syndrome.Sindrom Ovarium Polikistik (SOP) merupakan kelainan endokrinopati yang paling sering ditemui dan dialami 5-10% wanita usia reproduktif. Diagnosis SOP berdasarkan Konsensus European Society of Human Reproduction and Embryology and the American Society for Reproductive Medicine. Pengertian menyeluruh mengenai patofisiologi SOP masih sukar dipahami. Sindrom heterogenitas memperkuat perubahan multifaktorial, sehingga pengobatan berfokus pada perbaikan klinis berdasarkan sasaran pasien dan dokter. Penggunaan obat insulin-sensitizing menjadi bidang yang menarik akhir-akhir ini. Metformin dapat mengurangi risiko hiperinsulinisme, diabetes mellitus tipe 2, dan sindrom metabolik.